Size effects in thin coarse-grained gold microwires under tensile and torsional loading. (1st April 2015) - Chen, Ying; Kraft, Oliver; Walter, Mario
Abstract: Size effects are widely observed in the mechanical behavior of materials at the micron scale. However, the underlying deformation mechanisms often remain ambiguous, particularly in the presence of strain gradients. Here, combined microstructural investigations and mechanical testing in tension and torsion on annealed polycrystalline gold microwires with diameters of 12.5, 15, 17.5, 25, 40 and 60 μm were performed to investigate the influence of specimen size, grain size, strain rate and loading conditions on the deformation behavior of the wires. The studies were focused on samples with fully recrystallized microstructures in order to minimize the influence of the deformation related to the fabrication process. In particular, we have prepared a set of wires with different diameters, where the wires were selected such that they have comparable stress–strain behavior in tension. In contrast to tensile loading, a systematic "smaller is stronger" sample size effect was observed for torsional loading. Since a grain size effect as well as diameter-dependent texture variations were found in this study, it is argued that the determined size effect is related to the graded loading and microstructural influences.